2018
DOI: 10.3390/ijerph15040811
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of General and Central Obesity and Associated Factors among North Korean Refugees in South Korea by Duration after Defection from North Korea: A Cross-Sectional Study

Abstract: Previous studies on obesity status among North Korean refugees (NKRs) have been limited. We investigated mean body mass index (BMI), waist circumference (WC), and general and central obesity prevalence among NKRs in South Korea (SK) by duration after defection from North Korea (NK), using cross-sectional data of the North Korean Refugee Health in South Korea (NORNS) study and compared these data with a sample from the general South Korean population (the fifth Korea National Health and Nutrition Examination Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…Three studies reported the prevalence of obesity and metabolic diseases. In comparison with South Korean natives (SKN), one study showed that the obesity and central obesity prevalence rate in North Korean refugee (NKR) men increased by duration after defection, and all the prevalence rates were comparable to those of SKN for both the genders after >10 years of defection (obesity prevalence NKR vs. SKN: men, 34% vs. 39%, p = 0.690; women, 23% vs. 27%, p = 0.794; central obesity, 21% vs. 24%, p = 0.642; and women, 22% vs. 20%, p = 0.382, respectively) [13]. Our results are similar with another study wherein the excess weight gain after defection was associated with metabolic syndrome with similar prevalence rate of metabolic syndrome between NKR and SKN (men, 19.7% vs. 26.2%, p = 0.134; and women, 17.2% vs. 16.6%, p = 0.757, respectively) [11].…”
Section: Ncd-related Studiesmentioning
confidence: 77%
See 4 more Smart Citations
“…Three studies reported the prevalence of obesity and metabolic diseases. In comparison with South Korean natives (SKN), one study showed that the obesity and central obesity prevalence rate in North Korean refugee (NKR) men increased by duration after defection, and all the prevalence rates were comparable to those of SKN for both the genders after >10 years of defection (obesity prevalence NKR vs. SKN: men, 34% vs. 39%, p = 0.690; women, 23% vs. 27%, p = 0.794; central obesity, 21% vs. 24%, p = 0.642; and women, 22% vs. 20%, p = 0.382, respectively) [13]. Our results are similar with another study wherein the excess weight gain after defection was associated with metabolic syndrome with similar prevalence rate of metabolic syndrome between NKR and SKN (men, 19.7% vs. 26.2%, p = 0.134; and women, 17.2% vs. 16.6%, p = 0.757, respectively) [11].…”
Section: Ncd-related Studiesmentioning
confidence: 77%
“…The summary of the characteristics of selected studies is presented in Table 1. It includes 18 quantitative studies [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and 4 qualitative studies [28][29][30][31]; among the quantitative studies, 5 studies report comparisons with South Korean people [11,[13][14][15]22]. The number of participants in these studies varied from 8 to 932 participants, and 54.6%-100% of them were women.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations